Validating the Asher-McDade score to assess facial aesthetic outcomes in 22 consecutive complete bilateral cleft lip repairs. Issue 3 (April 2021) - Thomson, R.M.; Azzopardi, E.; Drake, D.
Abstract: Most scoring systems used to assess facial aesthetics in cleft patients tend to lack consistency, and the absence of an internationally agreed system makes comparison challenging. The most widely used and validated tool is the five-point Asher-McDade index. We note that there are currently no reports (to our knowledge) of its use for scoring outcomes after bilateral cleft lip repair. To validate it for this use, the aim was to describe the outcomes of 22 consecutive bilateral cleft lip repairs assessed using this scale. A retrospective review was undertaken of 22 consecutive patients with bilateral cleft lip repairs performed at our centre. Each patient underwent bilateral advancement rotation repair with a vomer flap on one side at three months followed by repair of the remaining hard palate and an intravelar veloplasty three months later. Standardised photographs were taken five years after repair and were cropped to isolate the nasolabial component. Eleven members of the cleft multidisciplinary team were asked to rate each image on a five-point Likert scale. Statistical analysis was performed using a two-way ANOVA test and intraclass correlation coefficient to interrogate intraobserver and interobserver variance. A total of 22 consecutive patients with complete bilateral cleft lips were photographed. The overall mean (range) score for the repairs was 3.2 (4.3 - 1.8). Two-way ANOVA demonstrated that inter-rater variability accounted for just over 10% (11.23% of the total variance, p < 0.0001). As predicted, the single biggest factor affecting score variability was the patient's appearance, which accounted for 44.51% of the total variance between scores (p < 0.0001). Intraobserver variance was not found to be significant, accounting for 0.33% of the total variance (p = 0.0006). We demonstrate that the Asher-McDade scoring system is a valid tool to use when assessing bilateral cleft lip repairs. Variance in the patient's score was significantly related to a true difference in appearance, with only a small percentage of differences being due to intraobserver and interobserver variation.